Kalvak (1901-1984) - Bushman, Leo (ARCTIC, 1988)
Kalvak, like other Inuit artists, dealt with and resolved the practical problems she was born to endure during her lifetime. The harsh north was home. As a practical woman with five daughters to care for, she conquered her world. As a matter of fact, according to her peer at Holman Island, "She was the best seamstress in the settlement." It was her ability and sensitivity to the art of sewing that spilled over into her arts and crafts ability. Kalvak could draw, and her drawings caught the eye of Father Henri Tardy, pioneer priest of the Oblate Order. Father Tardy encouraged her interests and developed and protected a collection of Kalvak's drawings, which he started collecting in the early 1960s. This collection became the nucleus of the print shop movement at Holman Island. . Kalvak was born in 1901 near Tahiryuak Lake on Victoria Island. She inherited the mythology and shamanism from her mother and traditional hunting skills from her father. Since she was the only surviving child of her parents, she became an early partner in the survival skills necessary in her environment. She learned early in life to fish and hunt. The mystique and love of Inuit culture were instilled by her mother. Both aspects of environmental forces and mystical lore fill Kalvak's drawings and prints. She was able to transpose several enigmatic sources into a simple drawing using the sun, the earth or the sea as symbols that express a feeling of her reference in time. As she herself was a very expressive person, her drawings take on the experienced expressions of her life.